Hubungan Pengetahuan Dan Personal Hygiene Dengan Kejadian Penyakit Kulit (Scabies) Di Pondok Pesantren Tahfidzul Qur’an Darul Falah Mamuju - Ahmad, Astriani Fauziah; Mappau, Zrimurti; Ahmad, Haeranah; Ashari, Agus Erwin (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2026)
This study aims to analyze the relationship between knowledge and personal hygiene and the incidence of scabies at the Darul Falah Tahfidzul Qur'an Islamic Boarding School, Mamuju, which has a high prevalence of symptoms but minimal health intervention. Using a quantitative design with a cross-sectional approach, this study involved 53 students who were selected through a total sampling technique. Data were collected using a structured questionnaire and analyzed by Chi-square test. The results showed a significant relationship between students' personal hygiene and the incidence of scabies (p-value = 0.001) while the knowledge variable did not show a significant relationship (p-value = 0.190). Based on these findings, it is recommended that behavior-based health interventions be implemented and strengthen the monitoring of the implementation of Clean and Healthy Living Behavior (PHBS) in the pesantren environment to effectively reduce the risk of scabies transmission.